Selective in-situ water removal by polybenzoxazole hollow fiber membrane for enhanced CO2 methanation - Kim, Eun Young; Hyeon, Myeong Hun; Wook Hwang, Hyun; Young Lee, Ji; Ki Kim, Seok; Bae, Youn Sang; Moon, Su Young (Chemical Engineering Journal, 2024)
In the Carbon Capture and Utilization (CCU) process, the conversion of captured CO2 into valuable chemicals and fuels, such as CO, CH3OH, CxHy, or CH4 represents a compelling alternative. These CO2 utilization reactions, utilizing hydrogen, produce H2O as a significant byproduct. This is detrimental as it diminishes reaction efficiency due to catalyst deactivation, water-based side reactions, and equilibrium limits. Although in-situ H2O removal can enhance product yield and reaction efficiency, selectively removing H2O at elevated reaction temperatures poses a considerable challenge. In this study, we synthesized polybenzoxazole (PBO) hollow fibers through the thermal treatment of hydroxyl polyimide and incorporated them into a fixed-bed reactor for CO2 methanation. The PBO membrane exhibited notable H2O permselectivity at elevated temperatures (350 ℃). When compared to a conventional reactor lacking the membrane, the PBO membrane reactor demonstrated increased CO2 conversion and CH4 selectivity owing to the selective removal of water.
Keywords: CH 4; CO2 methanation; Hollow-fibre membrane; Membrane reactor; MOF catalyst; Polybenzoxazole; Reaction efficiency; Valuable chemicals; Water removal; ]+ catalyst; CO2 methanation; Hollow fiber membrane; Membrane reactor; MOFs catalyst; Polybenzoxazole; Water removal